Legal Power of Deeds of Officers Making Legal Defective Land Deeds - Rodli, Achmad; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Legal actions stated by the parties in the deed made by the PPAT have evidentiary power but do not guarantee freedom from disputes between other interested parties, as is often seen in buying/selling transactions. This study aims to analyze the role of the Land Deed Making Officer (PPAT) in providing legal certainty through the making of valid deeds in accordance with applicable legal provisions. The research methods used are normative, legal, and conceptual. The results of the study indicate that deeds made by PPAT have an important role in ensuring legal certainty for land rights holders. However, there is a risk of legal defects that may arise due to non-compliance with applicable provisions. In addition, court decisions that confirm violations of the law by PPAT indicate the need for increased supervision and law enforcement of PPAT practices. This study recommends the need for ongoing PPAT training and strengthening regulations to prevent violations and increase public trust in the land registration system.Keywords: Making Official Land Deeds, Legal Certainty, Authentic Deeds, Land and Building Tax, Legal Violations.